How does form-meaning mapping develop over a period of 8 months in the three languages of an Afrikaans - German - South African English trilingual toddler? - Rousseau, Jo-Anne (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.